UX Design for the Visually Impaired to Improve Health Information Accessibility - Jin Kim, Woo; Ji Kim, Min; Kon Kim, Il (International Journal of Engineering and Technology, 2018)
This study was conducted on individuals with low vision, who constitute the highest population among visual impairment patients. We conducted an experiment to determine whether there was an improvement in accessibility to visual information for the visually impaired after applying the UX design guidelines. Additionally, we analyzed whether this UX design affects the information recognition rate for the non-disabled individuals.Â